Efficient method for the synthesis of methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate - Salunke, D. B.; Hazra, Braja G.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Pore, V. S. (Tetrahedron, 2005)
The synthesis of methyl 11 alpha-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate, methyl 11 beta-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate and methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate have been achieved. Mechanistic aspects for the decomposition of steroidal azidoketones to its enamines are discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 11-aminosteroid; 11-azidosteroid; base catalyzed epimerization; HIV-1 protease inhibitors; steroidal enamines

Stereoselective synthesis of (2R, 3S, 22R, 23E)-6, 6-ethylenedioxy-22-hydroxy-2, 3-isopropylidenedioxy-24-methyl-5 alpha-cholest-23-ene: An intermediate for the synthesis of castasterone, dolichosterone and brassinolide - Hazra, Braja G.; Kumar, T. P.; Pore, V. S. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2005)

Amino functionalized novel cholic acid derivatives induce HIV-1 replication and syncytia formation in T cells - Salunke, Deepak B.; Ravi, D. S.; Pore, V. S.; Mitra, Debashis; Hazra, Braja G. (Journal of Medicinal Chemistry, 2006)
Synthesis of C-11 azido/amino functionalized cholic acid derivatives has been achieved in excellent yields. Contrary to the previous prediction of analogous compounds to be HIV-1 protease inhibitors, in the present study these novel cholic acid derivatives induced host cell fusion during the progress of HIV-1 infection and produced multinucleated giant cells. This is the first report of syncytia induction and enhancement of viral replication in HIV-1 infected T cells by cholic acid derivatives.